NOAA/WDS Paleoclimatology - Wilson - Tagish - PCGL - ITRDB CANA606 - Wilson, R.J.S.; Luckman, B.H. (NOAA National Centers for Environmental Information, 2020)
This archived Paleoclimatology Study is available from the NOAA National Centers for Environmental Information (NCEI), under the World Data Service (WDS) for Paleoclimatology. The associated NCEI study type is Tree Ring. The data include parameters of tree ring with a geographic location of Yukon Territory, Canada. The time period coverage is from 383 to -55 in calendar years before present (BP). See metadata information for parameter and study location details. Please cite this study when using the data.